RANCANG BANGUN APLIKASI PENGAJUAN PEMBUATAN KTP ONLINE BERBASIS WEB DI KELURAHAN ARGASUNYA KOTA CIREBON - Kencana, Junaedi Surya; Dwilestari, Gifthera; Dana, Raditya Danar; Ajiz, Abdul; Kaslani (MEANS (Media Informasi Analisa dan Sistem), 2022)
Argasunya village is an institution responsible for the management of community data in a government environment. The need for public service will involve the state as a public service provider and individual citizens as recipients. But there is no application about the design of the application for the creation of E-KTP online, for that the author tried to make the Final Task regarding the Application for Submission of E-KTP Online which until now has not existed in Argasunya Village. In the process of collecting data with the aim to solve the problem, the author uses methods with data collection techniques, namely by observation and interview. And to design the application, the author used prototype development methods. In order to solve the problem, an application was made to make E-KTP Online. The final result obtained in this study is an application that can make it easier for people to create E-KTP. With some of the advantages that this application has, the application for the creation of E-KTP Online should be able to further alleviate the tasks given to the village. It is expected that this application will always be well controlled in terms of accuracy and data validation can be accounted for so that the information generated will be even better.